ACHIEVEMENTS IN SCIENCE OF WOMEN WORKING IN THE MEDICAL EDUCATION SYSTEM - Rayimova Nargiza (Western European Studies, 2025)
This article provides information about the contribution of women to the field of medical education, the role of candidates of sciences, doctors of sciences, that is, women working alongside men in the field of education in Uzbekistan.
Keywords: Medical education; Best Teacher of the Year; medical college